You lucky dog - London, Julia (Lucky dog, 2020)
"An accidental dog swap unleashes an unexpected love match . . . . Carly Kennedy is drowning in work, her divorced parents are going through their midlife crises, and somehow Carly's sister convinces her to foster Baxter-a basset hound rescue with a bad case of the blues. When Carly comes home from work to discover that the dog walker has accidentally switched out Baxter for another basset hound, she reaches the end of her leash. When Max Sheffington finds a depressed male dog in place of his cheerful Hazel, he is bewildered. But when cute, fiery Carly arrives on his doorstep, he is intrigued. Carly was not expecting a handsome, bespectacled man to be feeding her dog mac and cheese. However, Baxter is besotted with Hazel, and Carly realizes she may have found the key to her pup's happiness. For his sake, she starts to spend more time with Hazel and Max, until she begins to understand the appeal of falling for your polar opposite"--